Estimating sea spray volume flux with a laser gauge in a self-consistent system - Wang, Gang; Ma, Hongyu; Babanin, Alexander V.; Zhao, Biao; Huang, Chuanjiang; Dai, Dejun; Qiao, Fangli (Frontiers in Marine Science, 2023)
Sea spray is one of the drivers of heat, mass, and gas exchange between the ocean and the atmosphere, and its volume flux could be estimated by the record of the laser intensity. In the laboratory experiments, the relationship between sea spray and laser intensity could be established since the returned laser intensity of the observing gauge and spray concentration can be observed instantaneously. However, the difficulty to generalize the laboratory result to field observations is that the measurement of sea spray is usually unavailable on the open seas. Recent studies introduced an environment variable (atmospheric extinction coefficient for instance) to relate the laser intensity to spray volume flux for both laboratory and field observations so that the relationship established in the laboratory experiments could be extended to open seas. These studies however gave estimations of great difference since the relationships between each pair of the variables (spray volume flux, laser intensity, and the atmospheric extinction coefficient) are considered separately. This work established a self-consistent system composed of the three variables, in which the relationship between each pair of the variables in the system is consistent with that deduced from their respective relationships with the third variable. Consistency here we means that if Y=f(X), Y=g(Z) and Z=h(X), then Y=g(h(X))=f(X) is expected. The consistency of the relationships ensures that the estimation of the sea spray volume flux from laser intensity is robust. We established self-consistent relationships for the variables in the system composed of laser intensity, environment variable, and sea spray volume flux, for both laboratory and field experiments. Among them, the relationship between wind speed and spray volume flux is a reasonable reflection of the physical properties in two ways: a threshold value of spray volume flux at low wind speeds and the saturation at strong wind speeds. For a uniform regression of wind speed onto spray volume, a dimensionless parameter concerning wind speed is needed.